Sex and the city : [videorecording (DVD)] : the movie - Parker, Sarah Jessica; Cattrall, Kim; Davis, Kristin, 1966-; Nixon, Cynthia (New Line Video, 2008)
We find Carrie, Samantha, Charlotte, and Miranda four years after the series ended.